Reading pictures a history of love and hate - Manguel, Alberto (Random House, 2000)
This book looks at the work of great artists--from the intensely familiar to the undiscovered--and examines the stories behind them, tracing the passage of life into art. For example, Pablo Picasso torments his mistress Dora Maar and then paints brilliant studies of her grief-crumpled face; these evolve into the weeping woman in his great indictment of fascism, Guernica. The author untangles what this story, and countless others, shows us of our twin impulses toward creation and destruction.